Inhibition of Protein Prenylation of GTPases Alters Endothelial Barrier Function - Aslam, Muhammad (Int J Mol Sci, 2019)
The members of Rho family of GTPases, RhoA and Rac1 regulate endothelial cytoskeleton dynamics and hence barrier integrity. The spatial activities of these GTPases are regulated by post-translational prenylation. In the present study, we investigated the effect of prenylation inhibition on the endothelial cytoskeleton and barrier properties. The study was carried out in human umbilical vein endothelial cells (HUVEC) and protein prenylation is manipulated with various pharmacological inhibitors. Inhibition of either complete prenylation using statins or specifically geranylgeranylation but not farnesylation has a biphasic effect on HUVEC cytoskeleton and permeability. Short-term treatment inhibits the spatial activity of RhoA/Rho kinase (Rock) to actin cytoskeleton resulting in adherens junctions (AJ) stabilization and ameliorates thrombin-induced barrier disruption whereas long-term inhibition results in collapse of endothelial cytoskeleton leading to increased basal permeability. These effects are reversed by supplementing the cells with geranylgeranyl but not farnesyl pyrophosphate. Moreover, long-term inhibition of protein prenylation results in basal hyper activation of RhoA/Rock signaling that is antagonized by a specific Rock inhibitor or an activation of cAMP signaling. In conclusion, inhibition of geranylgeranylation in endothelial cells (ECs) exerts biphasic effect on endothelial barrier properties. Short-term inhibition stabilizes AJs and hence barrier function whereas long-term treatment results in disruption of barrier properties.